Performance Analysis and Optimization for Energy-Efficient Cooperative Transmission in Random Wireless Sensor Network - Li, Bin; Li, Hongxiang; Wang, Wenjie; Yin, Qinye; Liu, Hui (IEEE transactions on wireless communications, 2013)
This paper considers random wireless sensor networks where nodes are distributed randomly and form clusters to transmit the packets to relay clusters using cooperative multi-input-multi-output (CMIMO) technique. First, we study CMIMO energy consumption and divide it into intra-cluster energy consumption and inter-cluster energy consumption. Then we focus on analyzing the system performance in terms of overall packet error rate (PER) and energy consumption. Based on system performance metrics, we propose a new node sleep strategy, where overall energy consumption is minimized by coordinating inter-cluster transmitting energy consumption and the number of sensor nodes in activation. Compared to existing works, our contributions are (1) we consider random distribution of nodes and get a closed-form expression of overall PER that simplifies the energy minimization problem; (2) we analyze the tradeoff between overall energy consumption and nodes active rate. In simulation, we investigate the relationships among nodes active rate, inter-cluster transmitting energy consumption and the overall energy consumption. Furthermore, we discuss how these parameters are affected by the nodes density, the inter-cluster transmitting distance, the cluster radius and the intra-cluster energy consumption. Finally, we validate that the proposed nodes sleep strategy has significant energy savings compared with non-sleep cooperative transmission and direct transmission.